KARAKTERISTIK DAN PERLINDUNGAN HUKUM KEKERASAN SEKSUAL BERBASIS ELEKTRONIK - Marshellyna Wijaya (The Juris, 2026)
Cyber Sexual Harrasment is sexual violence that occurs through digital and has complex different characteristics from conventional sexual violence. The Characteristic is include the anonymity of the perpetrators, the massive and cross-border distribution of content, and the durability of the content which allows the violence to occur repeatedly. Even though Indonesia has regulated Cyber Sexual Harassment through UU TPKS and UU ITE the implementation of legal protection for victims is still not optimal. Obstacles include the lack of a fast and effective content removal mechanism, as well as the unequal understanding of the context of digital violence among law enforcement officials. These overall conditions indicate a gap between legal norms and their implementation in the field, so that protection for victims of KSBE tends not to reach the specific needs of victims in the digital space. Therefore, a comprehensive evaluation of the effectiveness of regulations and law enforcement is needed so that justice for victims does not stop at the normative level alone.